2020
DOI: 10.1016/j.meegid.2020.104493
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Time to exonerate the pangolin from the transmission of SARS-CoV-2 to humans

Abstract: The emergence of COVID-19 has triggered many works aiming at identifying the animal intermediate potentially involved in the transmission of SARS-CoV-2 to humans. The presence of SARS-CoV-2-related viruses in Malayan pangolins, in silico analysis of the ACE2 receptor polymorphism and sequence similarities between the Receptor Binding Domain (RBD) of the spike proteins of pangolin and human Sarbecoviruses led to the proposal of pangolin as intermediary. However, the binding affinity of the pangolin ACE2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 63 publications
1
99
0
2
Order By: Relevance
“…The hypothesis of pangolin ( M. javanica ) as an intermediate host for SARS-CoV-2 quickly became mainstream ( 32 , 44 ). We recently demonstrated that pangolin is unlikely to be the intermediate host and that transmission to humans could just as easily have taken place via another animal ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis of pangolin ( M. javanica ) as an intermediate host for SARS-CoV-2 quickly became mainstream ( 32 , 44 ). We recently demonstrated that pangolin is unlikely to be the intermediate host and that transmission to humans could just as easily have taken place via another animal ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…The snake hypothesis was quickly ruled out ( 32 ). Although the pangolin hypothesis was the mainstream, it was also recently excluded ( 33 , 34 ). At the same time, other species were singled out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They should rather be compared on the basis of their respective likelihood, but these would currently be very difficult to estimate, in the absence of key information, in particular on the precise experiments performed in China on closely related viruses before the pandemic. Besides, the pangolin hypothesis has now been strongly questioned (Lee et al 2020 ; Choo et al 2020 ; Frutos et al 2020 ). Regarding the hypothesis of reverse engineering, even though it is not obvious to identify any trace a posteriori there are currently several traceless options for genetic engineering.…”
Section: Current Status: the Jury Is Still Outmentioning
confidence: 99%
“…There is a unique feature of SARS-CoV-2 S protein which possesses a polybasic furin cleavage site at the junction of S1 and S2 subunits. This feature is believed to have emerged during viral transmission from zoonotic host to human 2527 , and is key to SARS-CoV-2 high transmissibility in humans 28,29 . Although robust SARS-CoV-2 infection of human lungs requires a multibasic cleavage site 30 , interestingly, both cleaved and uncleaved versions of S protein co-exist on virions purified from viral culture on Vero cells 31,32 .…”
Section: Introductionmentioning
confidence: 99%